Restoring the Oceanic Island Ecosystem Impact and Management of Invasive Alien Species in the Bonin Islands - Kawakami, Kazuto; Okochi, Isamu; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
The Bonin (Ogasawara) Islands, part of a remote Japanese archipelago, are a typical hot spot of biological invasion. Indigenous fauna and flora, which had long evolved in isolation, suffered devastating deforestation and invasion by multiple alien species in the twentieth century. Studies on the impacts of green anoles, flatworms, goats, cats, black rats, and tree and shrub species, among others, have led to new policies in an attempt to arrest the irreversible damage to the island biota. This book provides an overview of the research findings and countermeasures necessary for the successful management of island ecosystems. Based in research conducted over multiple species, this work provides scientists, researchers, students, and policy makers a unique perspective on the integration of conservation projects running simultaneously in the Bonin Islands and on the diversity of their impacts. Restoring ecosystems through the management of alien species is an important conservation issue and the dream that prompted this book.
The Bonin Islands -- What's the Bonin Islands? -- Impacts of Invasive Alien Species -- Impacts of Invasive Alien Species on Native Ecosystems on the Bonin Islands -- The cause of mollusk decline on the Ogasawara Islands -- Rapid decline of endemic snails in the Ogasawara Islands, Western Pacific Ocean -- Food habit of Platydemus manokwari De Beauchamp, 1962 (Tricladida: Terricola: Rhynchodemidae), known as a predatory flatworm of land snails in the Ogasawara (Bonin) Islands, Japan -- High Predation Pressure by an Introduced Flatworm on Land Snails on the Oceanic Ogasawara Islands -- Potential impacts of the invasive flatworm Platydemus manokwari on arboreal snails -- Impacts of Predation by the Invasive Black Rat Rattus rattus on the Bulwer's Petrel Bulweria bulwerii in the Bonin Islands, Japan -- Morphological and ecological shifts in a land snail caused by the impact of an introduced predator -- Bird predation by domestic cats on Hahajima Island, Bonin Islands, Japan -- Feral cat predation on seabirds on Hahajima, the Bonin Islands, Southern Japan -- High population densities of an exotic lizard, Anolis carolinensisand its possible role as a pollinator in the Ogasawara Islands. -- Why have endemic pollinators declined on the Ogasawara Islands? -- Vegetation changes between 1978, 1991 and 2003 in the Nakoudojima island that had been disturbed by feral goats -- Seed and seedling demography of invasive and native trees of subtropical Pacific islands -- Effects of an alien shrub species, Leucaena leucocephala, on establishment of native mid-successional tree species after disturbance in the national park in the Chichijima island, a subtropical oceanic island -- Countermeasure Against Invasive Species -- Management of Invasive Alien Species in the Bonin Islands -- Species Diversity and Conservation of Mandarina, an Endemic Land Snail of the Ogasawara Islands -- Hot water tolerance of soil animals: utility of hot water immersion in preventing invasions of alien soil animals -- Endemic Insects in the Ogasawara Islands: Negative Impacts of Alien Species and a Potential Mitigation Strategy -- A decrease in endemic odonates in the Ogasawara Islands, Japan -- Ecology and Control of the Green Anole (Anolis carolinensis), an Invasive Alien Species on the Ogasawara Islands -- Eradication and Ecosystem Impacts of Rats in the Ogasawara Islands -- Eradication of the Invasive Tree Species Bischofia javanica and Restoration of Native Forests on the Ogasawara Islands -- Predicting future invasion of an invasive alien tree in a Japanese oceanic island by process-based statistical models using recent distribution maps -- Beetle responses to artificial gaps in an oceanic island forest: implications for invasive tree management to conserve endemic species diversity -- Implications for Island Ecosystem Management -- Reconstruction of the Ecosystem in the Bonin Islands.
Keywords: Life sciences; Ecology; Biodiversity; Botany; Zoology; Nature Conservation; Life Sciences; Ecology; Biodiversity; Nature Conservation; Zoology; Plant Sciences